Simulação numérica de escoamentos com troca de calor no interior de tubos com nervuras periódicas - Ortiz, Carlos Enrique Pico (2002)
With the aim of develop a computational tool for thermodynamic optimization of heat exchangers, a computational code was implemented to solve the Navier-Stokes equations in an axisymmetric domain using the finite volume method and central differencing with Runge-Kutta explicit temporal advance and pressure-velocity coupling of fractional step type. This work presents results of the numeric simulation of the fully developed flow with heat transfer in a tube of circular section with ribs or obstacles, periodically spaced in the flow direction. The simulations were carried out in two regimes, laminar and turbulent, out of the completely rough region, and in four different geometries. In the cases with the high Reynolds number, the Smagorinsky subgrid model with damping function was used to include the effects of the quasi-two-dimensional scales not solved. In both cases, the primitive variables were decomposed to use periodic boundary conditions in the flow direction and non-slip boundary conditions in the walls. The results obtained in laminar regime are satisfactory. In the turbulent regime the results show the deficiency of the Smagorinsky subgrid model, when it is applied in two-dimensional domains.